ЩОДО ПИТАННЯ ПРО ІНФОРМАЦІЙНО-ПРАВОВЕ ЗАБЕЗПЕЧЕННЯ НАПРЯМКІВ ДІЯЛЬНОСТІ ОРГАНІВ ПРОКУРАТУРИ УКРАЇНИ - Сергій, Гайдай (SUPREMANCE OF LAW, 2018)
In the article is provided the theoretical substantiation of the information provision of the prosecutor’s offices of Ukraine by defining the legal nature, role and sources of information in the procedural and managerial activities. Among other things, the author defines an influence of information processes, information technologies and information exchange to the prosecutor activity, as a public person, in the information-legal state. In the conclusions the author provides suggestions for improving prosecutor’s law in the information sphere.
Keywords: prosecutor’s office; information law; prosecution’s information; information activity; off cial information; professional information